Existence of solitary waves in nonlocal nematic liquid crystals. (April 2015) - Zhang, Guoqing; Ding, Zhonghai
Abstract: In this paper, we study the solitary waves in nonlocal nematic liquid crystals. By applying the Mountain Pass Theorem and the Krasnoselskii genus theory, we prove some existence and multiplicity results of radially symmetric solitary waves.